Impact and transformation of education policy in China - Wiseman, Alexander W. (International Perspectives on Education and Society, 15., 2011)
This volume of the International Perspectives on Education and Society is the only book publishing research that traces the evolution of China's educational policy changes in the past three decades during which China experienced the greatest social-econom.